Development of mathematics learning devices with a problem based learning model oriented on the mathematics problem solving ability - Meryannav Sabilah; Fitriana Yolanda (International Journal of Trends in Mathematics Education Research, 2022)
The aims of this study is to produce a mathematical learning device with a Problem Based Learning model oriented to mathematical problem-solving abilities on the subject matter of the size of the concentration and distribution of valid and practical data for class VIII SMPN 1 Rengat Barat. This research on the development of mathematics learning tools uses a 4-D model, namely: 1) Define, 2) Design, 3) Develop, and 4) Disseminate. The data collection instruments used were RPP validation questionnaire sheets and LKPD validation questionnaire sheets and practicality sheets. The data collection technique used was non-test with a questionnaire validation of learning devices. The analytical technique used is descriptive statistical analysis. From the results of the study, it was obtained that the average value of RPP validation was 88.73% with a very valid category, while the validation in terms of RPP aspects obtained an average value of 89.24% with a very valid category. The results of the analysis of the average validation of LKPD are 87.5% with a very valid validation level, while the validation in terms of aspects obtained an average value of 87.98% with a very valid category. The average practicality of learning tools obtained a value of 85.4% with very practical category. Based on this study, it was found that the mathematics learning device with the Problem Based Learning model oriented to mathematical problem-solving abilities on the subject matter of the size of concentration and data distribution of class VIII students of SMPN 1 Rengat Barat has been tested for validity and practicality.